Does stress affect nonverbal engagement in teams? A case study in professional team sport. Issue 3 (1st November 2019) - Serpell, Benjamin G.; Larkham, Stephen; Cook, Christian J.
Abstract : Purpose: Team effectiveness is often predicated by a group's ability to communicate. However, the effect of stress response on communication success, particularly nonverbal engagement, and how this might affect team performance, is not clear; a "phenomenon" this study sought to explore. Design/methodology/approach: This was an observational study in a cohort of professional rugby players. Participants gave presentations to their peers on two separate occasions during a "live-in" camp designed to have psychologically stressful elements. Presentations were video recorded and audience engagement was measured. Testosterone and cortisol were used as biomarkers of stress response, with a high testosterone–cortisol ratio considered positive. A team training session followed the presentations and participants were rated for training quality. Findings: A small decline in testosterone was observed each day after waking. Conversely, cortisol rose after waking, with the rise being the highest on the first day. A decline in testosterone–cortisol ratio was also seen each day after waking; the decline was greatest on the first day. Presentation duration and audience engagement was greatest for the second presentation; when the testosterone-cortisol ratio decline and the cortisol increase after waking was smaller. Training quality was also better that day. Pooled data revealed a moderate inverse relationship and weak positive relationships for audience engagement with post-meeting cortisol and post-meeting testosterone–cortisol ratio, respectively. Training quality was related to testosterone and testosterone–cortisol ratio, but inversely related to cortisol. Originality/value: This study suggests that in stressful conditions, as suggested by an awakening hormone response, communication and team performance could become compromised with reduced ability to engage with others.